Work Process Based Learning and Serious Games – Didactical Concepts and Objectives for Competency Development - Spöttl, Georg; Schulte, Sven (International Journal of Advanced Corporate Learning (iJAC), 2015)
Work processes represent an important contentual basis for competency development within contemporary further training approaches in Germany and worldwide. This article underpins this and shows the importance of work process orientation for interlinking learning and working with the aim to develop competencies. At the same time the contemporary technological opportunities open up new forms of learning. Hence a gamification trend is emerging which brings Serious Games approaches to the further training approaches and strategies for personnel development of companies. The article reveals the pedagogical principles behind this approach, some first ideas which have been realized within the framework of a concrete project as well as the didactical challenges which still remain to be tackled.